Anti-Escherichia coli activity of extracts from Schinus terebinthifolius fruits and leaves. Issue 11 (3rd June 2018) - da Silva, Jessica H. S.; Simas, Naomi K.; Alviano, Celuta S.; Alviano, Daniela S.; Ventura, José A.; de Lima, Eliandro J.; Seabra, Sergio H.; Kuster, Ricardo M.
Abstract: Ethanol extracts obtained from Schinus terebinthifolius Raddi fruits and leaves were active against Escherichia coli with MIC of 78 μg mL −1 for both extracts. Phytochemical analyses revealed a major presence of phenolic acids, tannins, fatty acids and acid triterpenes in the leaves and phenolic acids, fatty acids, acid triterpenes and biflavonoids in the fruits. Major compounds isolated from the plant, such as the acid triterpene schinol, the phenolic acid derivative ethyl gallate and the biflavonoids agathisflavone and tetrahydroamentoflavone, showed very little activity against E. coli . Bioautography of the ethanol extracts on silica gel plate showed inhibition zones for E. coli . They were removed from the plate and the compounds identified as a mixture of myristic, pentadecanoic, palmitic, heptadecanoic, stearic, nonadecanoic, eicosanoic, heneicosanoic and behenic fatty acids. Abstract :